Impact of thermo‐tactile stimulation on the speed and efficiency of swallowing: a systematic review. Issue 4 (22nd March 2018) - Schwarz, Maria; Ward, Elizabeth C.; Ross, Jane; Semciw, Adam
Abstract: Background: A delayed or absent swallow reflex is common in dysphagia and can have a significant impact on swallow safety. Recent clinical practice survey data have supported the fact that clinicians continue to use thermo‐tactile stimulation (TTS) as a strategy to stimulate key nerve pathways and evoke a swallow reflex for patients with a delayed or absent swallow reflex. Aims: To conduct a systematic review of the effectiveness of TTS as a compensatory and/or rehabilitative tool. Methods & Procedures: A search performed on CINAHL, Medline and Speech Bite identified 599 articles. After removing duplicates, the titles and abstracts of 458 articles were assessed for eligibility; 426 articles were deemed to be clearly ineligible and the remaining 32 full‐text articles were further screened for inclusion. Ten of these studies were included in this review. Main Contribution: The results of this review highlight the lack of available evidence in this area and give support to the view that there is only low‐level evidence for use of TTS as a compensatory strategy immediately before a swallow. Conclusions & Implications: There is low‐level evidence to support the use of TTS. Current best practice would be to use TTS on a case‐by‐case basis, following detailed instrumental assessment and evaluation of its efficacy for an individual.